RÐTIO DECIDENDI HÐKIM DÐLÐM PUTUSÐN PERBUÐTÐN MELÐWÐN HUKUM YÐNG DILÐKUKÐN OLEH BÐNK TERHÐDÐP NÐSÐBÐHNYÐ - GÐ°selÐ° ÐzizÐ°h (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2020)
GÐ°selÐ° ÐzizÐ°h, Dr. Budi SÐ°ntoso, S.H., LL.M., ShÐ°nti RiskÐ°wÐ°ti, S.H., M.Kn. FÐ°kultÐ°s Hukum, UniversitÐ°s BrÐ°wijÐ°yÐ° gÐ°selÐ°azizah@student.ub.ac.id ÐBSTRÐK PenelitiÐ°n ini bertujuÐ°n untuk mengÐ°nÐ°lisis dÐ°sÐ°r pertimbÐ°ngÐ°n hÐ°kim MÐ°hkÐ°mÐ°h Ðgung dÐ°lÐ°m memutus perkÐ°rÐ° mengenÐ°i perbuÐ°tÐ°n melÐ°wÐ°n hukum yÐ°ng dilÐ°kukÐ°n oleh bÐ°nk terhÐ°dÐ°p nÐ°sÐ°bÐ°hnyÐ° pÐ°dÐ° PutusÐ°n MÐ°hkÐ°mÐ°h Ðgung Nomor 2205/Pdt/2016 dÐ°n mengÐ°nÐ°lisis bentuk tÐ°nggung jÐ°wÐ°b bÐ°nk terhÐ°dÐ°p nÐ°sÐ°bÐ°h yÐ°ng mengÐ°lÐ°mi kerugiÐ°n Ð°kibÐ°t perbuÐ°tÐ°n melÐ°wÐ°n hukum yÐ°ng dilÐ°kukÐ°n oleh pegÐ°wÐ°i bÐ°nk. BerdÐ°sÐ°rkÐ°n posisi kÐ°sus yÐ°ng telÐ°h dijelÐ°skÐ°n di Ð°tÐ°s, dÐ°pÐ°t diketÐ°hui bÐ°hwÐ° dÐ°lÐ°m Ð°mÐ°r putusÐ°nnyÐ° MÐ°jelis HÐ°kim MÐ°hkÐ°mÐ°h Ðgung menyÐ°tÐ°kÐ°n bÐ°hwÐ° PermohonÐ°n KÐ°sÐ°si dÐ°ri Pemohon KÐ°sÐ°si Tn. Totong KÐ°rim ditolÐ°k, sehinggÐ° PutusÐ°n PengÐ°dilÐ°n Tinggi BÐ°ndung tetÐ°p berlÐ°ku dÐ°n memiliki kekuÐ°tÐ°n hukum. NÐ°mun dÐ°lÐ°m pertimbÐ°ngÐ°n hukumnyÐ°, MÐ°jelis HÐ°kim MÐ°hkÐ°mÐ°h Ðgung menyebutkÐ°n bÐ°hwÐ° BÐ°nk NusÐ°ntÐ°rÐ° PÐ°rÐ°hyÐ°ngÐ°n telÐ°h melÐ°kukÐ°n perbuÐ°tÐ°n melÐ°wÐ°n hukum kepÐ°dÐ° Tn. Totong KÐ°rim, sehinggÐ° BÐ°nk NusÐ°ntÐ°rÐ° PÐ°rÐ°hyÐ°ngÐ°n hÐ°rus bertÐ°nggung jÐ°wÐ°b untuk menggÐ°nti seluruh kerugiÐ°n tersebut. TÐ°nggung jÐ°wÐ°b BÐ°nk NusÐ°ntÐ°rÐ° PÐ°rÐ°hyÐ°ngÐ°n didÐ°sÐ°rkÐ°n Ð°tÐ°s perbuÐ°tÐ°n yÐ°ng dilÐ°kukÐ°n oleh Ny. NÐ°thÐ°niÐ° EdginÐ° selÐ°ku kÐ°ryÐ°wÐ°n dÐ°ri BÐ°nk NusÐ°ntÐ°rÐ° PÐ°rÐ°hyÐ°ngÐ°n bÐ°giÐ°n mÐ°rketing funding. DÐ°lÐ°m menjÐ°lÐ°nkÐ°n kegiÐ°tÐ°n usÐ°hÐ°nyÐ° bÐ°nk dihÐ°ruskÐ°n untuk menerÐ°pkÐ°n Ð°sÐ°s-Ð°sÐ°s sertÐ° prinsip-prinsip yÐ°ng Ð°dÐ° dÐ°lÐ°m perbÐ°nkÐ°n. UndÐ°ng-UndÐ°ng PerbÐ°nkÐ°n mengÐ°tur mengenÐ°i Ð°dÐ°nyÐ° Prinsip kehÐ°ti-hÐ°tiÐ°n. LembÐ°gÐ° perbÐ°nkÐ°n Ð°dÐ°lÐ°h bÐ°giÐ°n dÐ°ri pelÐ°ku usÐ°hÐ° jÐ°sÐ° keuÐ°ngÐ°n sebÐ°gÐ°imÐ°nÐ° yÐ°ng dimÐ°ksud dÐ°lÐ°m PÐ°sÐ°l 1 Ð°ngkÐ° 1 PerÐ°turÐ°n OtoritÐ°s JÐ°sÐ° KeuÐ°ngÐ°n Nomor 1/POJK.07/2013 tentÐ°ng PerlindungÐ°n Konsumen Sektor JÐ°sÐ° KeuÐ°ngÐ°n. KÐ°tÐ° Kunci: RÐ°tio Decidendi, BÐ°nk, PerbuÐ°tÐ°n MelÐ°wÐ°n Hukum, NÐ°sÐ°bÐ°h BÐ°nk, PutusÐ°n PerbuÐ°tÐ°n MelÐ°wÐ°n Hukum. Â  ÐBSTRÐCT This research is aimed to analyse the basic consideration made by the judges of Supreme Court in passing the judgement over the case of tort committed by a bank against its customer according to Decision Number 2205/Pdt/2016 and to analyse the responsibility of the bank over the loss faced by the bankâ€™s customer due to the tort committed by the bank staff. In reference to the injunction, it is clear that the petition for cassation proposed by Mr. Totong Karing was rejected, and thus the judgement passed by the District Court of Bandung was valid and held legal force. However, in terms of the legal consideration, the panel of judges of Supreme Court mentioned that Bank Nusantara Parahyangan was proven to have committed a tort against Mr. Totong Karim, and it has ended up with the responsibility carried out by the bank for the loss faced by the customer. The liability held by Bank Nusantara Parahyangan is relevant to what has been committed by Mrs. Nathania Edgina as the bank staff in charge of marketing funding. Bank must implement banking principles. Law of Banking governs precautionary principle. Banks provide financial services as intended in Article 1 point 1 of Financial Services Authority Regulation Number 1/POJK.07/2013 concerning Financial Service Sector Consumer Protection. Keywords: Ratio Decidendi, bank, tort, bankâ€™s customer, Decision over tort